Guiding curriculum development: the need to return to local control - Norton, M. Scott (Rowman & Littlefield Publishers, 2016)
This book's primary purposes center on the need for placing the responsibility for determining student curriculum and academic achievement the local school level whereby school personnel determine the individual student's personal interests and needs and design a curricular program for each student that fosters personnel success.